2009
DOI: 10.1590/s0102-695x2009000400007
|View full text |Cite
|
Sign up to set email alerts
|

Atividade antioxidante das folhas de espinheira-santa - Maytenus ilicifolia Mart. ex Reiss., secas em diferentes temperaturas

Abstract: RESUMO:Maytenus ilicifolia Mart. ex Reiss, a espinheira-santa verdadeira, é largamente utilizada para tratamento de gastrites e úlceras estomacais. O seu valor terapêutico é atribuído principalmente aos polifenóis (flavonóides e taninos) e triterpenos. Os polifenóis são bastante estudados e estão relacionados à atividade antioxidante exercida pela planta. Existem vários métodos para avaliar a atividade antioxidante, a qual pode ser medida a capacidade antioxidante total utilizando o método de formação do compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2
15

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 18 publications
0
14
2
15
Order By: Relevance
“…where Abs (sample) is the absorbance of the solution of synthesized compounds and DPPH, Abs (blank) is the absorbance of methanol, and Abs (control) is the absorbance of the solution of methanol and DPPH [19].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where Abs (sample) is the absorbance of the solution of synthesized compounds and DPPH, Abs (blank) is the absorbance of methanol, and Abs (control) is the absorbance of the solution of methanol and DPPH [19].…”
Section: Methodsmentioning
confidence: 99%
“…Some papers have demonstrated that the compounds exhibiting antioxidant activity could be used as anticancer drugs, or as antiaging and anti-inflammatory agents [13][14][15]. The DPPH method is used extensively to evaluate antioxidant activity, and it has presented reliable results [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Infusion: 1-2 g (1-2 tea spoons) in 150 mL (tea cup) (Brasil, 2010c) Use 1 cup tea, 3 or 4 times daily (Brasil, 2010c) Treatment of gastritis and stomach ulcers (Negri, Possamai, Nakashima, 2009). …”
Section: Espinheira Santa (P T)mentioning
confidence: 99%
“…Thus, Radünz et al (2003) evaluating how several drying temperatures interfere in coumarin content of Mikania glomerata leaves, observed that samples dried at 50 ºC presented a minor change regarding the plant in natura. Leaves of Maytenus ilicifolia ("espinheira-santa"), grown under the sun, were dried by Negri (2007) in an incubator at temperatures of 40, 50, 60, 70 and 80 o C. When dosing polyphenols, it was concluded that drying temperatures influence total polyphenol and tannin contents, recommending lower temperatures for this process. Diniz et al (2007) assessed the drying effect on the amount of flavonoids and hypericin in vegetative parts of Hypericum perforatum L. (hypericum).…”
Section: Flavonoid Contentsmentioning
confidence: 99%